Sapir & Whorf’s Socio-Cultural Tradition (Eurasian Journal of Learning and Academic Teaching, 2023)
The paper focuses on the Edward Sapir and Benjamin Whorf as major proponents of the theory. The theory is hinged on the idea that cultural aspects are manifest in language and thus communication; and to them, communication can never be understood in isolation, that culture should be part and parcel in the endeavor.